Comparison of Factorial and Taguchi’s Methods In Optimization of Effective Parameters of Coal Flotation - Rezai, B.; Sheibi, H.; Refahi, A.; Ghomi, M. Fatemi (Asian Journal of Chemistry, 2010)
In this work, the aspects of experimental design is described in two Taguchi’s and Factorial methods and applied to optimized four factors that affecting flotation of coal (pulp density, impeller speed, the amount of gasoline and pine oil) and determined that the results of Taguchi’s method with performing a few experiments, are suitable than Factorial method. In factorial method, pulp density and pine oil assuming factors have no effect on the result of experiments, however in Taguchi's method, four factors have more effect on the results.